DOMENIUL EDUCAȚIONAL: DE LA MOTIVAȚIE SPRE CARIERĂ - Ornoveţchii, Tatiana (Print-Caro, 2021)
Education is one of the most important parts in a human's life. Education gives us the possibility to evolve in different domains, to discover new and useful things. To be motivated to build a career in education means to have the desire for changes and for progress. Education is an international priority and each society must have the interest to promote knowledge. Today, to be a teacher is a real challenge, because it means to change a pupil's live and to be involved in a social responsibility. Building a teaching career is a complicated way of achieving society’s balance and harmony. Teaching career involves a strong intrinsic and extrinsic motivation and also a real force of altruism.
Keywords: Education; motivation; career; progress